When Taiwan’s Fate Changed Dramatically in the 1940s: The Price of War, the Nationalists’ Game, and the Vagaries of International Politics - Chevalérias, Philippe (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2014)
This article reviews and assesses the scale and impact of the political and economic watersheds experienced by Taiwan from the late 1930s to the early 1950s. After examining the physical damage and human losses brought about by the Second World War and explaining the economic slump following the island’s return to Chinese rule, the article highlights the post-1949 dilemmas faced by the Nationalist, American, and Japanese governments to arbitrate between political and geo-strategic/economic interests. The division across the Strait forced Taiwan to resume economic relations with Japan far more rapidly that might have been expected, which made it possible to compensate, within a very short period of time, for the loss of Chinese market, while Japanese firms were able to establish strong and lasting relations with Taiwanese businessmen. In addition, the provision of American raw materials, consumption goods, and public capital contributed greatly to economic development and political stability on the island at a time when recovery was still ongoing. Quand le destin de Taiwan s’est radicalement transformé dans les années 1940 : le prix de la guerre, le jeu des nationalistes et les aléas de la politique internationale Cet article évalue l’ampleur et l’impact des bouleversements politiques et économiques qui ont frappé Taiwan entre la fin des années 1930 et le début des années 1950. Après avoir exposé les dégâts matériels et les pertes humaines causés par la Seconde Guerre mondiale et analysé la crise économique engendrée par le retour de l’île sous souveraineté chinoise, l’article met en évidence les dilemmes auxquels ont été confrontés les gouvernements nationaliste chinois, américain et japonais après 1949 pour arbitrer entre différents intérêts politiques et économico-géostratégiques. La fermeture des relations entre les deux rives du Détroit a contraint Taiwan à renouer, plus rapidement que prévu, ses relations économiques avec le Japon, ce qui lui a permis de compenser en peu de temps la perte du marché chinois, tandis que les entreprises japonaises ont pu établir des relations durables avec leurs homologues taiwanaises. En outre, la fourniture, par les Etats-Unis, de matières premières, de biens de consommation et de capitaux a contribué à la relance économique et à la stabilité politique de l’île.